Impacto de la pandemia por Covid 19 en el embarazo y sus repercusiones perinatales: una revisión sistemática. - Vargas-Linares, A.J. (2024)
Since its inception, the COVID-19 infection has impacted the lives of at-risk populations, including pregnant women. Using clinical data and case studies, other authors have shown greater morbidity in pregnant women positive for the infection. This review includes articles from the PUBMED, SCOPUS, and SCIENCEDIRECT databases of international research. Data have shown that, compared to uninfected pregnant women, COVID is associated with increased risk and maternal and perinatal complications. Complications involving increased hospital admission were present mostly in the third trimester and included premature birth, spontaneous abortion, cesarean section, ICU admission, assisted mechanical ventilation, pneumonia, maternal death. Birth outcomes often included fetal distress, intrauterine death, and perinatal events found were low birth weight, severe sepsis, and neonatal death. The risk of vertical transmission is low. Few findings show pregnant women asymptomatic to the infection and this depends on whether the pregnant woman has other comorbidities such as obesity, high blood pressure, diabetes mellitus that increase the risk of maternal morbidity and mortality.